Real-time dynamic evolution monitoring of laser-induced exciton phase flips in 2D hybrid semiconductor (C12H25NH3)2PbI4 - Mohammad Adnan (2020)
Real-time monitoring of room-temperature exciton photoluminescence (PL) while irradiated with ultrafast laser excitations (UV and infrared) in long alkyl-chain based (C12H25NH3)2PbI4 inorganic–organic hybrid semiconductors is presented. These naturally self-assembled 2D hybrid structures show strong room-temperature Mott-type excitons confined within the lowest inorganic bandgap, which are highly sensitive to structural phase flips. Under both one-photon (E1PA ≥ Eg) and two-photon (2E2PA ≥ Eg) laser excitations, the exciton PL of unstable phase-II appears initially, and with prolonged laser exposure, the PL peak switches to a new stable blueshifted phase-I peak position. This exciton phase flip demonstrates different laser-induced structural deformations in inorganic quantum wells (PbI6 extended network) associated with orthorhombic (phase-I) and monoclinic (phase-II) unit cells. One-photon absorption induced PL shows the various time dynamics of laser exposure depending on laser characteristics (continuous wave and ultrashort pulsed lasers), mostly influenced by localized heating, ablation effects, and third-order nonlinear effects such as saturation of linear absorption and exciton–exciton annihilation. However, in two-photon absorption induced PL, the near infrared laser excitation reveals the redshifted crumpled excitons from the deeper depth of the sample, which are induced by multiphoton absorption and avalanche ionization. A series of systematic linear and nonlinear steady-state and time-resolved PL studies are presented. A simplified kinetic model further provides an understanding of the real-time evolution of laser-induced excitons and their related phase flips. These laser-induced exciton phase flips and linear and nonlinear optical probing open a new avenue for novel functional properties and nonlinear absorption–based optoelectronic devices.